Changes in the legal environment and enforcement of firearm transfer laws in Pennsylvania and Maryland. (13th January 2018) - Crifasi, Cassandra K; Merrill-Francis, Molly; Webster, Daniel W; Wintemute, Garen J; Vernick, Jon S
Abstract : The effectiveness of laws depends on circumstances affecting their enforcement. To assess such circumstances for comprehensive background check (CBC) and straw purchase laws for firearm sales, we examined prosecutions for CBC and straw purchase violations in Pennsylvania and CBC violations in Maryland. We generated pre-post variables and conducted t-tests to assess differences in the mean number of prosecutions filed following changes to the legal environments. The annual number of prosecutions for straw purchase violations increased significantly in Pennsylvania following the passage of a law that strengthened penalties for these violations (difference in means = +1310.86, P=0.003). The annual number of prosecutions for CBC violations decreased significantly in Maryland following a court decision that narrowed the definition of a firearm transfer making enforcement more difficult (difference in means = −20.52, P=0.026). Our findings suggest enforcement is likely influenced by the penalties associated with violating these laws and the interpretation of the language of the laws.